Less Is More? The Impact of Trauma Volume on the Positive Rate of Head Computed Tomography Scans in Head Trauma Patients. (18th June 2012) - Chen, Chao-Wen; Lou, Yun-Ting; Chu, Chi-Ming; Lin, Hsing-Lin; Lee, Wei-Che; Ma, Ke-Zong; Cheng, Yuan-Chia; Kuo, Liang-Chi
Abstract : Objective . Few studies have assessed the impact of trauma volume on the operational efficiency of emergency departments. Herein, we evaluate the association between trauma volume with the positive rate of head computed tomography scans in head trauma patients in a tertiary care hospital. Methods . This is a retrospective cohort review involving all head trauma patients presenting to a tertiary care hospital. Trauma census, head trauma patient volume, the number of emergent head CT scans, and the number of positive head CT scans were collected on a monthly basis. Comparison was primarily made between the trauma patient volume and the positive rate of head CT scans. Results . 25, 549 trauma patients were reviewed. Of these, 5, 168 (20.2%) sustained head trauma and 3, 336 head CT scans were performed with mean 29.1% positive rate of substantial head injuries. The monthly data were analyzed and a statistically significant correlation between monthly trauma volume and decrease in positive rate of head CT scan was identified (Pearson r = − 0.51, P = 0.02 ). With introducing different cut-point values of trauma volume, we identified the threshold of trauma census as approximately 4.9 and 8.8% higher than mean monthly trauma volume in discriminating significant decrease of positive rate of head CT scans.